2010
DOI: 10.1002/pola.24253
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of fluorinated polybenzoxazoles with low dielectric constants

Abstract: Two fluorinated aromatic bis(o-aminophenol)s, 1,1bis(3 0 -amino-4 0 -hydroxyphenyl)-1-(3 0 -trifluoromethylphenyl)-2,2, 2-trifluoroethane (6FAP) and 1,1-bis(3 0 -amino-4 0 -hydroxyphenyl)-1-(3 0 ,5 0 -ditrifluoromethylphenyl)-2,2,2-trifluoroethane (9FAP) were synthesized, which were allowed to polycondense with aromatic diacyl chlorides to afford the fluorinated aromatic polybenzoxazoles (PBOs) via a conventional two-step procedure in which the low-temperature solution polycondensation process was first perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…Compared with kapton-IF70 film (the dielectric constant is 3.6 at 10.1 GHz), all these PI films had lower dielectric constants (2.60 to 2.93) and dielectric losses (3.9 × 10 −3 to 10.2 × 10 −3 ). 30 Silicon atoms are larger than carbon atoms, Si O bond is more flexible than C C bond, and flexibility of aliphatic siloxane chain is higher than that of the general polyimide chain. The molecular polarity of polymer, 10 the volume of molecular chains, 11 and the arrangements between the molecular chains affect the dielectric constant of polymer.…”
Section: Thermal Behaviors Of Pi Filmsmentioning
confidence: 99%
“…Compared with kapton-IF70 film (the dielectric constant is 3.6 at 10.1 GHz), all these PI films had lower dielectric constants (2.60 to 2.93) and dielectric losses (3.9 × 10 −3 to 10.2 × 10 −3 ). 30 Silicon atoms are larger than carbon atoms, Si O bond is more flexible than C C bond, and flexibility of aliphatic siloxane chain is higher than that of the general polyimide chain. The molecular polarity of polymer, 10 the volume of molecular chains, 11 and the arrangements between the molecular chains affect the dielectric constant of polymer.…”
Section: Thermal Behaviors Of Pi Filmsmentioning
confidence: 99%
“…13 They have also achieved a k value of 2.57 at 1 MHz in fluorinated PBO. 14 However, the simultaneously increased chain flexibility in such polymers could result in increased CTE, and the synthesis of highly fluorinated monomers for polymerization was usually costly and complicated. The k values of polymers could also be reduced by the creation of nanoscale or microscale pores in matrix through hard or soft template methods.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] It is the rigid-rod polymer chains that endow PBO with these super properties, however, it inevitably makes PBO incompliant with common processing, because PBO can neither be dissolved in common solvents nor melt before decomposition. For example, it is shown that the incorporation of fluorine atoms in aromatic polymers, such as PI, could improve its solubility, 12 while the fluorinated PBO was not always soluble in organic solvent, 13 which may be because of the higher interchain packing ability of benzoxazole groups as compared to imide rings, flexible bonds were further needed to reduce the chain rigidity. 7 Moreover, despite it is recognized that PBO is an ideal reinforcing agent for polymer composites, the insoluble feature of PBO makes it only possible to reinforce polymer matrix in the form of fibers, while unable to directly incorporate the rigid-rod chains into polymers on molecular level.…”
Section: Introductionmentioning
confidence: 99%